Biofuel production from olive mill wastewater through its Ni/Al2O3 and Ru/Al2O3 catalyzed supercritical water gasification - Kipcak, Ekin; Akgun, Mesut (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This article presents the findings of our research regarding the supercritical water gasification of a real biomass, olive mill wastewater, with Ni/Al2O3 and Ru/Al2O3 catalysts. The experiments were performed at five reaction temperatures between 400 and 600 degrees C, for five reaction times ranging from 30 to 150 s and at a constant pressure of 25 MPa. It was seen that the employment of catalysts enhanced the gasification and biofuel production yield, which mainly involved methane and hydrogen. NilAl(2)O(3) was selective for hydrogen formation, whereas Ru/Al2O3 favored the formation of methane. The highest calorific value of the produced biofuel was obtained as 56123 kj/m(3) with Ru/Al2O3 at 600 degrees C and 60 s. Apart from biofuel production, the simultaneous treatment of the wastewater was also accomplished. At elevated temperatures and times, treatment efficiencies greater than 97% based on total organic carbon conversion were reached. Moreover, the kinetic evaluation of the catalytic supercritical water gasification of olive mill wastewater was performed based on first order reaction kinetics. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biofuel; Ni/Al2O3; Ru/Al2O3; Olive mill wastewater; Supercritical water; HOT COMPRESSED WATER; HYDROGEN-PRODUCTION; SEWAGE-SLUDGE; BIOMASS GASIFICATION; TEMPERATURE; GLUCOSE; LIGNIN; COMBUSTION; EFFLUENTS; CELLULOSE; Science & Technology - Other Topics; Energy & Fuels